Current Status of Libraries In India: A Study on the Current Status of Libraries in India (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Some 10,000 year ago the early ancestor of mankind,subsisted by hunting and gathering, started to building agrarian societies. Theold agrarian societies began their transitions to industrial societies inmid-18th centuries (3). Expansion of intellectual activities in industrialsocieties, such as industrial production, international trade and transactions,and technological advancement, stimulated mass distribution of education and creationof libraries.